A tale of two women: The Caribbean orchid portraits of Louise Auguste von Panhuys (1763–1844) and Nancy Anne Kingsbury Wollstonecraft (1791–1828) - Ossenbach, Carlos (2025)
Louise von Panhuys (1763–1844) and Nancy Anne Kingsbury Wollstonecraft (1791–1828) stand out historically as the first female illustrators of neotropical orchids. Louise von Panhuys epitomized an era when high social status equated to a refined education; as the writers of her time described, a classic “lady of leisure.” In contrast Nancy K. Wollstonecraft, was the daughter of a clergyman from New England, born into the broad American middle class which shaped the early decades of the United States’ independent life. Both shared a common passion for: the exuberant forests of the Caribbean European colonies: von Panhuys in the Dutch territory of Suriname and Wollstonecraft in the Spanish island of Cuba. The artistic result of these two women’s works is astounding and went in different directions: while von Panhuys painted to entertain herself and with a mostly descriptive purpose, Wollstonecraft combined her artistic talent and her botanical knowledge into a three-volume manuscript, Specimens of the Fruits and Plants of the Island of Cuba (unfortunately never published), with accurate and detailed descriptions and beautiful illustrations. Biographies of these two extraordinary women are accompanied by complete sets of their orchid paintings, eight by Panhuys (along with several of her landscapes and scenes from Suriname) and nine by Wollstonecraft. A clarifying note: Wollstonecraft’s name is indistinctly given as ‘Nancy Anne’, ‘Anne’, or ‘Nancy’. The author has adhered to the name as given in the different bibliographical sources.